Clinical efficacy and safety of venetoclax combined with hypomethylating agents in relapsed high-risk acute myeloid leukemia patients after allogeneic hematopoietic stem cell transplantation - Cheng, Jiaying; Fu, Haipeng; Jiang, Ling; Huang, Yun; Zhang, Yujiao; Long, Zhiquan; Jiang, Xuejie (Frontiers in Medicine, 2025)
IntroductionRelapse after allogeneic hematopoietic stem cell transplantation (allo-HSCT) for high-risk myeloid malignancies remains a major therapeutic challenge, with conventional chemotherapy offering limited survival benefits. BCL-2 inhibition combined with hypomethylating agents (HMAs) has emerged as a potential therapeutic option, but comparative data in this setting are scarce.MethodsWe conducted a single-center retrospective study of 106 consecutive patients with post-transplant acute myeloid leukemia (AML) recurrence treated between 2020 and 2024. Patients received either venetoclax plus HMAs (n = 53) or intensive chemotherapy (n = 53). Outcomes assessed included complete remission (CR) rate, overall survival (OS), measurable residual disease (MRD) clearance, and treatment-related toxicities. Multivariable Cox regression analysis was performed to evaluate survival predictors.ResultsThe venetoclax-based regimen achieved significantly higher CR rates (56.6% vs. 26.4%, p = 0.002) compared with intensive chemotherapy. Median OS was markedly improved with venetoclax plus HMAs (12.6 vs. 5.8 months; HR 0.42, p < 0.001). MRD clearance was more frequent in the venetoclax group (70.0% vs. 35.7%, p = 0.021). Safety analysis demonstrated lower incidences of severe cytopenias (36.8% vs. 64.2%, p = 0.002) and infectious complications (11.3% vs. 32.1%, p = 0.008). Multivariable modeling confirmed venetoclax-based therapy as an independent predictor of improved survival (adjusted HR 0.42, 95% CI 0.31–0.58).DiscussionVenetoclax in combination with HMAs provided superior clinical benefits over intensive chemotherapy in post-allo-HSCT AML relapse, achieving higher remission rates, improved survival, enhanced MRD clearance, and a favorable safety profile. These findings highlight venetoclax-based regimens as a promising therapeutic approach for this high-risk population.